IoT gateway for AR/VR application using Li-Fi transmission - Wong, Calvin Ren Jie (Nanyang Technological University, 2021)
In a world where the Internet of Things are becoming much more important and prominent in our lives, there are growing concerns and higher demands regarding the speed, reliability, and security aspects of a network. Furthermore, as more and more users globally start to gain access to the Internet, there is a correlated increase in the number of connections tapping into any respective network. This may result in heavier traffic, causing the connection to become less reliable and efficient. Malicious users may also acquire confidential data sent over the network if ample measures are not taken to help keep the connection secure. The main support for wireless communications is mostly through the use of radio waves, however, there are also other types of waves that can be used. For example, light waves are one of them. Light Fidelity (Li-Fi) is the technology where data is transmitted using light-emitting devices such as LED light bulbs. With Li-Fi, if the user is unable to see the light, they will not be able to access the data transmitted which helps prevent unauthorized access into the network by malicious users. Li-Fi is also capable of allowing each range of light to be used as a single bandwidth by a single user. In this project, we aim to explore the possibilities of implementing Light Fidelity (Li-Fi) in Virtual Reality (VR) and/or Augmented Reality (AR) environments.